The oncological outcome of the patients with ovarian clear cell cancer: Platinum-based adjuvant chemotherapy is not suitable - Çakır, Caner; Kılıç, Fatih; Kılıç, Çiğdem; Yüksel, Dilek; Korkmaz, Vakkas; Kimyon Cömert, Günsu; Türkmen, Osman; Turan, Taner (Journal of Surgery and Medicine, 2021)
Background/Aim: Ovarian clear cell cancer (OCCC) is one of the rare histological subtypes of epithelial ovarian cancer with different tumoral biology and prognosis. This study aimed to evaluate the clinical and pathological data of OCCC and define the prognostic factors. Methods: Sixty-three patients with OCCC were included in this retrospective cross-sectional study. Patients with mixed-type clear cell carcinoma were excluded. Response to chemotherapy was assessed according to the WHO criteria. The survival analysis was performed using the Kaplan-Meier method and survival curves were compared with the log-rank test. Cox proportional hazards model was used in the multivariate analysis. Results: The mean age of patients was 54.6 (10.7) years. Twenty-three (36.5%) patients were stage III&IV. Systematic lymphadenectomy was performed in 55 (87.3%) patients and 13 (23.6%) had lymph node metastasis. Maximal cytoreduction was performed in 57 (90.5%) patients, optimal cytoreduction, in 1 (1.6%) patient, and suboptimal cytoreduction was performed in 2 (3.2%) patients via primary cytoreductive surgery. The complete clinical response rate following adjuvant treatment was 61.1% in stages III&IV. Five-year failure-free survival was 63% in the entire cohort. According to the multivariate analysis, the stage was an independent risk factor for treatment failure. The probability of recurrence increased 24 times in stages III and IV (95% Confidence interval: 5.561-104.421; P<0.001). Conclusion: The stage of the disease is a prognostic factor for OCCC. The response to platinum-based chemotherapy in OCCC is very low.